Mapeamento das instituições de custódia e arquivos permanentes e históricos existentes no município de Manaus - Silva Neta, Luzia Acácio da (Brasil, 2024)
In this work, which has as its main objective the mapping of custody institutions and permanent and historical archives existing in the city of Manaus, a survey of institutions in the city was carried out and subsequently a search for means of contact with these institutions. The return from the institutions was considered low, being somewhat detrimental to the result to be delivered, but it served as a way of informing readers about some important aspects of the city of Manaus so that the reader knows in what environment these custodian mission holders these permanent archives are situated.